Real-time controller design and onboard attitude estimation of a quadrotor with collision safety through ultrasonic sensors - Rumshaa Yunus (International Journal of Advanced Robotic Systems)
Quadrotors are small-sized, inexpensive aerial systems widely used for various indoor operations. Stable flight is a challenge for quadrotors due to low-cost sensors and indoor flight safety constraints add to their complexity. In this study, an Arduino based quadrotor is designed to test 2nd order Complementary filters for state estimation along with a controller with collision safety for indoor flight. Ultrasonic sensors are used for object detection during flight. Detailed hardware assembling along with the implementation of Complementary filter and PID controller is discussed. System tunning is done using the Heuristic method and system response is tested in real time. This study proves that by using the above techniques, a stable flight is achieved with collision safety using ultrasonic sensors.